Serie van 3 foto's. Tentoonstelling in Ons Huis t.g.v. 85-jarig jubileum van NVAAD afd. Rotterdam - Vroege, J.,
Serie van 3 foto's. Tentoonstelling in Ons Huis t.g.v. 85-jarig jubileum van NVAAD afd. Rotterdam.